2011
DOI: 10.1158/1078-0432.ccr-10-0890
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Autophagy Augments In Vitro and In Vivo Antimyeloma Activity of DNA-Damaging Chemotherapy

Abstract: Purpose: Although autophagy occurs in most tumor cells following DNA damage, it is still a mystery how this DNA-damaging event turns on the autophagy machinery in multiple myeloma (MM) and how the functional status of autophagy impacts on its susceptibility to death in response to DNA-damaging chemotherapy.Experimental Design: We investigate the effects of DNA damage on autophagy in MM cells and elucidate its underlying molecular mechanism. Then, we examined the impacts of pharmacologic or genetic inhibition o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 50 publications
6
66
0
Order By: Relevance
“…In MM cells, hypersecretion of monoclonal immunoglobulin caused aggregation of numerous unfolded proteins, leading to endoplasmic reticulum stress and autophagy activation (Yang et al, 2011). In addition, a previous study (Pan et al, 2011) confirmed that DNAdamaging reagents such as DOX and melphalan can mediate the activation of autophagy. Based on this information, autophagy may be of great significance in the drug resistance of MM cells.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In MM cells, hypersecretion of monoclonal immunoglobulin caused aggregation of numerous unfolded proteins, leading to endoplasmic reticulum stress and autophagy activation (Yang et al, 2011). In addition, a previous study (Pan et al, 2011) confirmed that DNAdamaging reagents such as DOX and melphalan can mediate the activation of autophagy. Based on this information, autophagy may be of great significance in the drug resistance of MM cells.…”
Section: Discussionmentioning
confidence: 81%
“…Autophagy inhibitors (8 mM hydroxychloroquine or 10 mM 3-methyladenine (Pan et al, 2011) were added to RPMI8226/DOX cells with DOX for 24 h to observe the effect of combined treatment on cells. The cells in each group were collected and adjusted to a density of 1 μM/mL.…”
Section: Detection Of Apoptosis By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that RPMI-8226 cells promote plasmacytomas in SCID mice. 23 However, whether this is due to a haematologica | 2012; 97(7) 0 1E3 1E4 1E5 0 1E3 1E4 1E5 CD19 CD27 CD38 CD45 CD56 CD138 CD19 CD27 CD38 CD45 CD56 CD138 +DEAB -DEAB CD20 -CD20 unfractionated (n=4) or CD20 depleted (n=4) RPMI-8226 cells into 8 CB17-SCID mice. We found that 100% of the mice in each group developed plasmacytomas without any difference in the growth pattern ( Figure 2C), suggesting that CD20 dim+ cells are not essential for tumor formation.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…7,8 Although apoptosis induction has been the major focus of research in novel MM therapies, a recent study documented a pivotal role for autophagy as a prosurvival mechanism in MM cells, suggesting its potential as an additional target for novel therapeutics. 9,10 Intracellular nicotinamide adenine nucleotide (NAD ϩ ) plays a major role in the regulation of several cellular processes. 11,12 In mammals, NAD ϩ is replenished from nicotinamide (Nam), tryptophan or nicotinic acid (NA), with Nam as the most important and widely available precursor.…”
Section: Introductionmentioning
confidence: 99%